2021
DOI: 10.3390/ma14081938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stirring Pin Rotation Speed on Microstructure and Mechanical Properties of 2A14-T4 Alloy T-Joints Produced by Stationary Shoulder Friction Stir Welding

Abstract: In this study, 2A14-T4 Al-alloy T-joints were prepared via stationary shoulder friction stir welding (SSFSW) technology where the stirring pin’s rotation speed was set as different values. In combination with the numerical simulation results, the macro-forming, microstructure, and mechanical properties of the joints under different welding conditions were analyzed. The results show that the thermal cycle curves in the SSFSW process are featured by a steep climb and slow decreasing variation trends. As the stir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This phenomenon, known as stirring action, provides valuable information about the internal defect formation [ 56 , 57 , 58 ]. The controlling stirring action during FSW of the T-configuration is essential to produce a sound joint [ 3 , 19 , 36 , 59 ]. The material velocity can change the share of the flange in the welding area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon, known as stirring action, provides valuable information about the internal defect formation [ 56 , 57 , 58 ]. The controlling stirring action during FSW of the T-configuration is essential to produce a sound joint [ 3 , 19 , 36 , 59 ]. The material velocity can change the share of the flange in the welding area.…”
Section: Resultsmentioning
confidence: 99%
“…The value of β is defined between 0 and 1, where 0 is used for a nonmixing situation, and 1 is used for a well-mixed situation. The percentage of heat transferred into the workpiece is related to the thermal conductivity, density, and heat capacity of both the tool and workpiece material and is calculated by [35]: γ = kρC p workpiece kρC p tool + kρC p workpiece (12) The heat flux continuity of the shoulder-workpiece interface is presented as [36]:…”
Section: Thermal Studymentioning
confidence: 99%
“…In Equation (17), ( ) is the effective strain rate, Q denotes activation energy, and R is universal gas constant [ 51 ]: where ε ij is the strain rate tensor [ 53 ]: …”
Section: Modeling Of Ufsw Processmentioning
confidence: 99%
“…Achieving high-strength dissimilar joints requires experimentation with effective FSW process conditions to minimize material mixing and processing temperature [8,9]. Several studies have explored the influence of process parameters, such as tool offset [10], welding speed [11], rotational speed [12], and the number of multi-passes [13,14], on IMC formation in Al-Ti FSW joints. Li et al [15] observed poor joint strength due to massive IMC formation from Al and Ti intermixing.…”
Section: Introductionmentioning
confidence: 99%